(untitled) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to faind out and examine how the mecanism of reseller agents and and promotion strategies through social media are appropriate by reseller agents. The data obtained are primary data. This research is a field research that uses a qualitative descriptive approach with the method of observation and structure interview. The results of the study include a reseller mechanism where the reseller promotes products through their social media at a certain price and when they receive an order, the supplier will send the goods to the buyer’s address or to the reseller’s addres. From these sales, the reseller can make a profit. Promotion strategies through social media that are carried out by resellers include having social media, good service, determining targets, and the right time for promotion. In addition, the procurement of discount promos and the inclusion of testimonials also needs to be done to attract consumer interest and increase sales.